E-suicide note: A newer trend and its medico-legal implications in India. (June 2014) - Behera, C; Karthik, Krishna; Dogra, TD; Lalwani, S; Millo, T; Singh, SR
Rapid advancements of information and communication technology in the form of electronic mails, mobile phones, social networking sites, etc have an increasing impact on people's day to day life. It has been observed that these readily available applications are used frequently to express suicidal intentions. There are many studies on conventional handwritten suicide notes but suicide note in electronic format is an emerging issue and an under-researched phenomena. The authors have termed it as "E-suicide note" and discuss its medico-legal implications in India with examples from their observations.